Down‐regulation of hepatic CYP3A1 expression in a rat model of indomethacin‐induced small intestinal ulcers. (14th October 2016) - Kawauchi, Shoji; Nakamura, Tsutomu; Horibe, Sayo; Tanahashi, Toshihito; Mizuno, Shigeto; Hamaguchi, Tsuneo; Rikitake, Yoshiyuki
Abstract: The liver and the small intestine are closely related in the processes of drug absorption, metabolism and excretion via the enterohepatic circulation. Small intestinal ulcers are a serious adverse effect commonly occurring in patients taking nonsteroidal anti‐inflammatory drugs. However, the influence of small intestinal ulcers on drug metabolism has not been established. This study examined the expressional changes of cytochrome P450 (CYP) in the liver using an indomethacin‐induced small intestinal ulcer rat model and in cultured cells. After the administration of indomethacin to rats, ulcers were observed in the small intestine and expression of CYP3A1, the major isoform of hepatic CYP, was significantly down‐regulated in the liver, accompanied by increased expression of inducible nitric oxide synthase, tumor necrosis factor α, interleukin (IL)‐1β and IL‐6, in the small intestine and the liver. The indomethacin‐induced small intestinal ulceration, the increase in inflammatory mediators in the small intestine and the liver, and the down‐regulation of CYP3A1 expression in the liver were inhibited by co‐administration of ampicillin, an antibacterial agent. In the human hepatic HepG2 cell line, IL‐1β, IL‐6 and NOC‐18, an NO donor, caused down‐regulation of CYP3A4, the major isoform of human CYP3A. Thus, this study suggests that after indomethacin treatment small intestinal ulcers cause the down‐regulation of CYP3A1 in the rat liver through an increase in ulcer‐derived inflammatory mediators. Copyright © 2016 John Wiley & Sons, Ltd.